The Heroes of Shukur Kholmirzayev's Stories and the Story of Bandi the Eagle - Boronov Ibrokhimbek Safarovich (Open Academia, 2023)
This article provides information about the characteristics of Shukur Kholmirzayev's stories and the story of Burgut.